UPAYA JAMAICA FORUM FOR LESBIANS, ALL-SEXUALS, AND GAYS (J-FLAG) DALAM MELAWAN HOMOPHOBIA DI JAMAIKA - Nurul Hidayah; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research explains about how the efforts Jamaica Forum for Lesbians, All-Sexuals, and Gays in against homophobia in Jamaica.J-FLAG is the foremost organisation in Jamaica advocating for the rights of lesbian, gay, bisexual and transgender (LGBT) people.Jamaica has a rich history of human rights advocacyfor the LGBT community. The movement began in the 1970s with the Gay Freedom Movement, spearheaded by Larry Chang who also later cofounded J-FLAG with several others. In those days, more pockets of tolerance and gay social spaces existed.Jamaica’s anti-sodomy or “buggery” laws that prohibit same-sex conduct betweenconsenting adult males date to 1864 when Jamaica was a British colony. Sections 76, 77 and 79 of the Offences Against the Person Act make the abominable crime of buggery.Prosecutions under these laws are rarely pursued. Nevertheless the laws have a real and negative impact. Criminalizing sexual intimacy between men offers legal sanction todiscrimination against sexual and gender minorities, and in a context of widespreadhomophobia, gives social sanction to prejudice and helps to create a context in whichhostility and violence is directed against LGBT people.Key Words: J-FLAG, Homophobia, LGBT, Buggery